Serial Activation of the Inducible Caspase 9 Safety Switch After Human Stem Cell Transplantation - Zhou, Xiaoou (Mol Ther, 2016)
Activation of the inducible caspase 9 (iC9) safety gene by a dimerizing drug (chemical inducer of dimerization (CID) AP1903) effectively resolves the symptoms and signs of graft-versus-host disease (GvHD) in haploidentical stem cell transplant (HSCT) recipients. However, after CID treatment, 1% of iC9-T cells remain and can regrow over time; although these resurgent T cells do not cause recurrent GvHD, it remains unclear whether repeat CID treatments are a safe and feasible way to further deplete residual gene-modified T cells should any other adverse effects associated with them occur. Here, we report a patient who received an infusion of haploidentical iC9-T cells after HSCT and subsequently received three treatments with AP1903. There was a mild (grade 2) and transient pancytopenia following each AP1903 administration but no non-hematological toxicity. Ninety five percent of circulating iC9-T cells (CD3(+)CD19(+)) were eliminated after the first AP1903 treatment. Three months later, the residual cells had expanded more than eightfold and had a lower level of iC9 expression. Each repeated AP1903 administration eliminated a diminishing percentage of the residual repopulating cells, but elimination could be enhanced by T-cell activation. These data support the safety and efficiency of repeated CID treatments for persistent or recurring toxicity from T-cell therapies.